The Influence of Music on the Congregation's Interest in Services at HKBP Sukadame Church Sukadame Resort Pematangsiantar - Bangun Munthe; Bangun; Jesika Sitorus (Bulletin of Science Education, 2024)
The main problem answered in this research is: How far does music influence the congregation's interest in church services. (Case: HKBP Sukadame Resort Sukadame Pematangsiantar). The number of samples taken from the population was 80 people, the research used descriptive methods while data analysis was carried out in hypothesis testing using Pearson product moment correlation, with the data collection tool being a questionnaire for variable X (Influence of music) and variable Y (congregation interest in church services). To find out the extent of the influence of music on the congregation's interest in church services. (Case: HKBP Sukadame Resort Sukadame Pematangsiantar), the Pearson product-moment correlation statistical test was used. From the test results, it was obtained that r = 0.71, while to determine whether the correlation coefficient was significant at the real level of 0.05, the "t" test was used with the test criterion if thit greater than ttab (3,96 > 1,67)  then the hypothesis is accepted. So, it can be stated that there is a significant relationship between the influence of music on the congregation's interest in church services (Case: HKBP Sukadame Resort Sukadame Pematangsiantar.